Reinforcement method for realizing self-flocculation settling separation of tailings based on flue gas desulfurization

By generating a slurry system with self-flocculation capability through the flue gas desulfurization process, the problems of low sedimentation and separation efficiency and difficulty in resource utilization in iron tailings treatment are solved, realizing an efficient tailings resource utilization and environmentally friendly separation method.

CN121243960APending Publication Date: 2026-01-02NORTHEASTERN UNIV CHINA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511813808.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-04
Publication Date
2026-01-02

AI Technical Summary

Technical Problem

Existing technologies have failed to effectively utilize iron tailings to treat flue gas and enhance subsequent solid-liquid sedimentation separation during the gas-solid separation process, resulting in high tailings treatment costs, significant environmental pollution risks, and difficulties in resource utilization.

Method used

Through the flue gas desulfurization process, the waste heat of the flue gas is used to react with the alkaline iron tailings slurry to generate a slurry system with self-flocculation ability, including sulfate crystals and amorphous iron hydroxide gel, which is directly used for the sedimentation and separation of tailings to enhance the solid-liquid separation efficiency.

Benefits of technology

It significantly improves the efficiency of tailings sedimentation and separation, reduces the amount of external flocculants used, lowers the overall cost of the separation process, realizes the resource utilization of tailings, and solves the environmental pollution problem.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121243960A_ABST
    Figure CN121243960A_ABST
Patent Text Reader

Abstract

The invention discloses a reinforcing method for realizing self-flocculation settling separation of tailings based on flue gas desulfurization, and belongs to the green and environment-friendly technical field of solid waste recycling and flue gas treatment. The method comprises the following steps: carrying out size mixing on iron tailings obtained through physical separation, then introducing roasting or steel smelting flue gas into ore pulp for desulfurization, and meanwhile, heating the ore pulp exposed in the air by utilizing flue gas waste heat, so that alkaline minerals in the ore pulp are converted into sulfate crystals; the method comprises the following steps of: oxidizing and hydrolyzing Fe < 2 + > in ore pulp to generate amorphous iron hydroxide gel and multi-core hydroxyl iron complex gel, so as to obtain an ore pulp system with self-flocculation capacity, and directly adding the ore pulp system into a thickening tank for settling separation of tailings. According to the invention, a closed-loop technical method of gas-solid separation and solid-liquid separation is constructed, the tailing slurry is used as a desulfurizing agent to complete flue gas purification and separation, and the internal biomass generated in the process is utilized to strengthen tailing settling separation, so that a brand new technical path is opened up for bulk and high-value utilization of iron tailings.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of green environmental protection technology of solid waste resource utilization and flue gas treatment, and particularly relates to a method for realizing self-flocculation and sedimentation separation of tailings based on flue gas desulfurization. BACKGROUND

[0002] With the rapid development of the steel industry, a large amount of iron tailings solid waste is produced in the process of iron ore beneficiation. According to statistics, 2.5 tons to 4.0 tons of iron tailings will be produced for every ton of iron concentrate produced. These tailings are usually treated by open-air stacking or tailings pond landfill, which not only occupies a large amount of land resources, but also poses a serious environmental risk: fine particle tailings are prone to dust pollution under dry climate conditions, and particles with a particle size of less than 75 μm can diffuse to the surrounding area through wind action to cause air PM2.5 and PM10 pollution; under the action of rainfall leaching, heavy metal ions (such as Pb, Cd, Cr, As, etc.) in the tailings can be dissolved and migrated to the surrounding water, causing potential pollution to groundwater and soil environment; in addition, there is a risk of dam breakage in the tailings pond.

[0003] A large amount of flue gas containing sulfur dioxide is produced in the process of iron ore roasting. SO2, as one of the main atmospheric pollutants, its emission will lead to the formation of acid rain, causing damage to the ecological system, and harm to the human respiratory system. The currently industrialized flue gas desulfurization technologies mainly include limestone-gypsum method, ammonia method, sodium alkali method, etc., but these methods all have obvious defects: the limestone-gypsum method has a relatively high desulfurization efficiency (usually > 95%), but produces a large amount of low-value gypsum byproduct (2.7 tons of gypsum are produced for every ton of SO2 removed), which is difficult to utilize comprehensively; the ammonia desulfurization method has the problem of ammonia escape, and the escaped ammonia reacts with SO3 to form ammonium sulfate aerosol, and the unreacted ammonia will cause secondary pollution; the sodium alkali method has high desulfurization efficiency, but has high running cost (the treatment cost is about 3000 yuan / ton to 5000 yuan / ton of SO2), and the produced mixture of sodium sulfite / sodium sulfate is difficult to be resourceized. These traditional desulfurization methods also have common problems such as complex system, easy scaling and plugging of equipment, high investment and running cost, etc.

[0004] In the tailings treatment link of the beneficiation plant, a large amount of flocculants is usually added to accelerate the sedimentation and water recycling of the tailings. This not only significantly increases the beneficiation cost (the cost of flocculants accounts for about 5% to 8% of the total beneficiation cost), but also affects the beneficiation index due to the accumulation of toxic flocculants through the water recycling system; at the same time, the introduction of aluminum ions and other inorganic flocculants may change the physicochemical properties of the tailings, affect the water quality, and even cause new pollution to the water body. Patent CN107213774A proposes to use copper tailings or red mud waste powder to treat smelting waste, and to make solid flocculants from the waste residue after flue gas desulfurization, but the invention needs to add an oxidizing solution, and is not suitable for the field of beneficiation.

[0005] At present, there is no method for treating flue gas with iron tailings and using gas-solid separation process to induce and strengthen subsequent solid-liquid sedimentation separation in situ. SUMMARY

[0006] In view of the deficiencies of the prior art described in the background art, the present application provides a method for realizing self-flocculation and sedimentation separation of tailings based on flue gas desulfurization, which takes flue gas desulfurization as the primary and necessary step, and through optimization of slurry concentration, reaction temperature, gas-liquid ratio and other operation parameters, achieves SO2 removal while inducing a synergistic reaction in the tailings slurry system, and the product can be directly used to strengthen the subsequent solid-liquid separation process, thereby significantly improving the efficiency of the entire separation system.

[0007] In the first aspect, the present application provides a method for realizing self-flocculation and sedimentation separation of tailings based on flue gas desulfurization, comprising the following steps:

[0008] Slurry is prepared from the iron tailings obtained by physical separation process to obtain alkaline iron tailings slurry;

[0009] The roasting or steel smelting flue gas is introduced into the alkaline iron tailings slurry to carry out flue gas desulfurization, and at the same time, the slurry exposed to air is heated by using the waste heat of the flue gas, the alkaline minerals in the slurry are converted into sulfate crystals, and the amorphous iron hydroxide gel and polynuclear hydroxyl iron complex gel produced by oxidation and hydrolysis of Fe 2+ The obtained slurry system with self-flocculation ability is directly added into the thickener tank for sedimentation separation of the tailings.

[0010] Wherein:

[0011] The iron tailings include magnetic separation iron tailings, pre-enrichment iron tailings, pre-throw tailings and gravity separation iron tailings, and the TFe grade in the iron tailings is > 5%.

[0012] The alkaline component in the iron tailings is ≥ 15 wt.%, and the particle size of the tailings is 60%~80% of -325 mesh; the alkaline component includes one or more of CaO and MgO.

[0013] The solid-liquid ratio of the alkaline iron tailings slurry is 1: (3~5), and the pH value of the slurry is 9~12.

[0014] When the pH value of the slurry is lower than 9, NaOH or Ca(OH)2 is added for adjustment.

[0015] The SO2 concentration in the roasting or steel smelting flue gas is 500 mg / m 3 ~5000 mg / m 3 The volume ratio of flue gas to slurry is (20~40): 1 m 3 / L, and the temperature of the slurry is 30℃~80℃.

[0016] The SO2 concentration in the desulfurized flue gas is ≤200 mg / m³. 3 It meets the special emission limits specified in the "Emission Standard of Air Pollutants for Iron and Steel Sintering and Pelletizing Industry" (GB 28662-2012), with a desulfurization efficiency of ≥90%; the solid content of the tailings after desulfurization is 20wt.%~30wt.%, and the pH value of the slurry is 6~9.

[0017] After the slurry system is directly added to the thickening tank for sedimentation, the initial sedimentation velocity of the tailings flocculation is ≥3m / h, and the amount of external flocculant used is reduced by more than 50% during the sedimentation process.

[0018] Secondly, the present invention proposes a slurry system with self-flocculation capability, which is prepared by the above method. The slurry system contains sulfate crystals as a framework and amorphous iron hydroxide gel and polynuclear hydroxy iron complexes loaded thereon. The sulfate crystals are selected from calcium sulfite crystals, magnesium sulfite crystals, calcium sulfate crystals and magnesium sulfate crystals.

[0019] The beneficial effects of this invention are:

[0020] 1. This invention constructs a closed-loop technology method for gas-solid separation and solid-liquid separation. This method uses tailings slurry as a desulfurizing agent to complete flue gas purification and separation, and utilizes the endogenous substances generated in the process to enhance tailings sedimentation and separation. It simultaneously solves two major environmental problems, significantly reduces the overall operating cost of the separation process, and opens up a new technical path for the large-scale and high-value utilization of iron tailings.

[0021] 2. This invention, through the gas-solid separation process of flue gas desulfurization, forms an in-situ solid-liquid separation multi-component synergistic system within the slurry that significantly enhances sedimentation, achieving synergistic enhancement of "charge neutralization-adsorption bridging-netting and sweeping":

[0022] (1) Charge neutralization and bridging: During the reaction, polynuclear hydroxy iron complexes (such as [Fe2(OH)2] are generated in situ through the dissolution and oxidation of iron ions. 4+ The amorphous Fe(OH)3 gel can efficiently neutralize the negative charge on the surface of tailings particles and form large and dense flocs through hydroxyl bridging.

[0023] (2) Netting, sweeping and crystal nucleation: The desulfurization products CaSO4·2H2O and CaSO3·0.5H2O microcrystals act as a flocculation skeleton, which can effectively net and sweep fine particles during the sedimentation process, significantly enhancing the sedimentation effect.

[0024] Compared to traditional methods that rely solely on external flocculants (such as PAM), the slurry system formed by this invention acts on the sedimentation of the thickening tank, which can reduce the amount of external flocculant used by more than 50%, and even achieve "zero external addition" under optimal conditions. At the same time, it increases the initial sedimentation velocity of tailings flocculation to more than 3m / h, improving efficiency by nearly 3 times.

[0025] 3. The process of this invention exhibits a significant synergistic enhancement effect. The entire method revolves around "separation," with SO2 in the flue gas serving as the sulfur source for the enhanced sedimentation separation system. The residual heat of the flue gas provides favorable temperature conditions for the reaction, promoting SO2 absorption, iron ion oxidation, and hydrolysis polymerization reactions. Iron tailings simultaneously serve as a desulfurization alkali source and an iron source (providing Fe for the formation of highly efficient flocculants). 2+ / Fe 3+ It serves as a carrier for flocculation systems and truly realizes the synergistic transformation and resource utilization of multiple elements such as sulfur, iron, calcium, and magnesium within an integrated separation method. Attached Figure Description

[0026] Figure 1 This is a process flow diagram of a tailings self-flocculation sedimentation separation enhancement method based on flue gas desulfurization according to the present invention. Detailed Implementation

[0027] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples.

[0028] An enhanced method for achieving self-flocculation and sedimentation separation of tailings based on flue gas desulfurization, the process flow is as follows: Figure 1 As shown, it includes the following steps:

[0029] Low-grade iron tailings obtained through physical separation are slurry-adjusted to obtain alkaline iron tailings slurry. The iron tailings include magnetically separated iron tailings, pre-enriched iron tailings, pre-disposal iron tailings, and gravity-separated iron tailings. The TFe grade in the iron tailings is >5%, the alkaline component is ≥15 wt.%, and the tailings particle size is -325 mesh, accounting for 60%~80%. The alkaline component includes one or more of CaO and MgO. The solid-liquid ratio of the alkaline iron tailings slurry is 1:(3~5), and the slurry pH is 9~12. When the slurry pH is lower than 9, NaOH or Ca(OH)2 is added for adjustment.

[0030] The chemical reaction formulas involved in the preparation process of alkaline iron tailings slurry are as follows:

[0031] CaO + H₂O → Ca 2+ +2OH - ;

[0032] MgO + H₂O → Mg 2+ +2OH - .

[0033] The flue gas from roasting or iron smelting is passed into an alkaline iron tailings slurry for flue gas desulfurization (gas-solid separation). Simultaneously, the waste heat from the flue gas is used to heat the slurry exposed to air. The SO2 concentration in the flue gas is 500 mg / m³. 3 ~5000mg / m 3 The volume ratio of flue gas to slurry is (20~40):1m³ 3 / L, pulp temperature is 30℃~80℃. This process induces changes in the physicochemical properties of the pulp; alkaline minerals in the pulp are transformed into sulfate crystals, which react with Fe in the pulp. 2+ The amorphous ferric hydroxide gel and polynuclear ferric hydroxy complex gel produced by oxidation and hydrolysis form components that can significantly enhance sedimentation and separation effects, resulting in a slurry system with self-flocculation capabilities.

[0034] The resulting slurry system is directly added to a thickening tank for tailings sedimentation and separation. The initial sedimentation velocity of tailings flocculation is ≥3m / h, and the amount of external flocculant used during sedimentation is reduced by more than 50%, which significantly enhances the solid-liquid separation efficiency in the sedimentation process.

[0035] In this process, the minerals in the slurry are transformed into sulfate crystals; under aeration or in the presence of dissolved oxygen, the Fe in the slurry... 2+ Oxidized to Fe 3+ Fe 3+ The various hydroxyl complexes produced by hydrolysis have excellent charge neutralization and bridging capabilities, forming a slurry system with sulfate crystals that has a flocculating effect.

[0036] SO2 concentration in flue gas after desulfurization ≤200mg / m³ 3 It meets the special emission limits specified in the "Emission Standard of Air Pollutants for Iron and Steel Sintering and Pelletizing Industry" (GB 28662-2012), with a desulfurization efficiency of ≥90%; the solid content of the tailings after desulfurization is 20wt.%~30wt.%, and the pH value of the slurry is 6~9.

[0037] The above-mentioned slurry system consists of a sulfate crystal framework, on which highly flocculating amorphous ferric hydroxide gel and polynuclear ferric hydroxy complex gel are loaded. Through the combined action of the crystalline phase and the amorphous gel phase, the slurry system achieves enhanced sedimentation and separation performance. The sulfate crystals are selected from calcium sulfite crystals, magnesium sulfite crystals, calcium sulfate crystals, and magnesium sulfate crystals.

[0038] The chemical reaction formulas involved in the flue gas desulfurization and slurry heating process are as follows:

[0039] (1) SO2 absorption and acid-base neutralization:

[0040] SO2(g) + H2O → H2SO3;

[0041] H2SO3 + 2OH - →SO3 2- +2H2O;

[0042] H2SO3+OH - →HSO3 - +H2O.

[0043] (2) Ca 2+ and Mg 2+ Precipitation forms sulfite / sulfate:

[0044] Ca 2+ +SO3 2- +0.5H2O→CaSO3·0.5H2O↓;

[0045] Ca 2+ +HSO3 - +OH - →CaSO3↓+H2O;

[0046] CaSO3+0.5O2+2H2O→CaSO4·2H2O↓;

[0047] Mg 2+ +SO3 2- +0.5H2O→MgSO3·0.5H2O↓;

[0048] Mg 2+ +HSO3 - +OH - →MgSO3↓+H2O;

[0049] MgSO3+0.5O2+2H2O→MgSO4·2H2O↓.

[0050] (3) Fe 2+ Oxidation:

[0051] 4Fe 2+ +O2 (from flue gas, aeration, or dissolved oxygen) + 2H2O → 4Fe 3+ +4OH - .

[0052] (4) Fe 3+ Hydrolysis and polymerization:

[0053] Fe 3+ +H2O Fe(OH) 2+ +H + ;

[0054] 2Fe 3+ +2H₂O→[Fe₂(OH)₂]4+ +2H + ;

[0055] Fe 3+ +3OH - →Fe(OH)3 (amorphous gel)↓.

[0056] Example 1

[0057] An enhanced method for achieving self-flocculation and sedimentation separation of tailings based on flue gas desulfurization, the process flow is as follows: Figure 1 As shown, it includes the following steps:

[0058] Iron tailings from a certain iron ore mine (basic components CaO+MgO content 18wt.%), with a TFe grade of 15.98%, were ground to -325 mesh (65%). The flue gas originated from a pyrite roasting furnace in the same mine, with a temperature of approximately 160℃ and an SO2 concentration of 1200 mg / m³. 3 .

[0059] (1) The magnetic separation iron tailings were slurried to obtain alkaline iron tailings slurry. The solid-liquid ratio of the alkaline iron tailings slurry was 1:4, that is, the slurry concentration was 20wt.% and the slurry pH value was 10.5.

[0060] (2) The hot flue gas from roasting is mixed at a volume ratio of 25:1 (m³ / kg / kg / m³). 3 / L) Alkaline iron tailings slurry is introduced into the bubble column for flue gas desulfurization. Simultaneously, the waste heat from the flue gas is used to heat the slurry exposed to air, maintaining a slurry temperature of 55±5℃. The alkaline minerals in the slurry are converted into sulfate crystals, which react with the Fe in the slurry. 2+ The amorphous ferric hydroxide gel and polynuclear ferric hydroxy complex gel produced by oxidation and hydrolysis form components that can significantly enhance sedimentation and separation effects, resulting in a slurry system with self-flocculation capabilities.

[0061] The resulting slurry system was directly added to a thickening tank for tailings sedimentation and separation. The initial settling velocity of the tailings flocculation reached 3.5 m / h, which is nearly 3 times higher than that of the same batch of untreated tailings slurry (settling rate of about 1.2 m / h). Moreover, it can meet the requirements of subsequent pressure filtration without the addition of any external flocculants.

[0062] In this process, the minerals in the slurry are transformed into calcium magnesium (sulfite) crystals; under aeration or in the presence of dissolved oxygen, the Fe in the slurry... 2+ Converted to Fe 3+ Fe 3+ The various hydroxyl complexes produced by hydrolysis have excellent charge neutralization and bridging capabilities, and work synergistically with calcium magnesium (sulfite) crystals.

[0063] After desulfurization, the SO2 concentration at the flue gas outlet stabilized at 45 mg / m³. 3The desulfurization efficiency reached 96.3%. The solid content of the tailings after desulfurization was 23.63 wt.%, and the pH value of the slurry was 7.8.

[0064] The resulting slurry system (the product of gas-solid separation) has calcium magnesium (sulfite) sulfite crystals as its framework, on which are loaded highly flocculating amorphous iron hydroxide gel and polynuclear hydroxy iron complex gel. The calcium magnesium (sulfite) sulfite crystals include calcium sulfite crystals, magnesium sulfite crystals, calcium sulfate crystals and magnesium sulfate crystals.

[0065] Example 2

[0066] An enhanced method for achieving self-flocculation and sedimentation separation of tailings based on flue gas desulfurization includes the following steps:

[0067] The tailings from vanadium-titanium magnetite gravity separation (alkaline components CaO+MgO content 16 wt.%) were used, with a TFe grade of 29.81% and 60% of the particles being -325 mesh. The flue gas source was secondary flue gas from a converter, with a temperature of approximately 140℃ and an SO2 concentration of 800 mg / m³. 3 .

[0068] (1) The vanadium-titanium magnetite gravity separation tailings were slurried to obtain alkaline iron tailings slurry. The solid-liquid ratio of the slurry was 1:5, that is, the slurry concentration was 16.7 wt.% and the pH value of the slurry was 9.8.

[0069] (2) The hot flue gas from roasting is mixed at a volume ratio of 40:1 (m³ / kg) 3 / L) Alkaline iron tailings slurry is introduced into the bubble column for flue gas desulfurization. Simultaneously, the waste heat from the flue gas is used to heat the slurry exposed to air, maintaining a slurry temperature of 50℃. The alkaline minerals in the slurry are converted into sulfate crystals, which react with the Fe in the slurry. 2+ The amorphous ferric hydroxide gel and polynuclear ferric hydroxy complex gel produced by oxidation and hydrolysis form components that can significantly enhance sedimentation and separation effects, resulting in a slurry system with self-flocculation capabilities.

[0070] The resulting slurry system is directly added to a thickening tank for tailings sedimentation and separation. The initial settling rate of the tailings reaches 3.2 m / h. Compared with the original process that required the addition of a large amount of PAM (0.8 kg per ton of dry tailings), only 0.3 kg / t of PAM is now needed to achieve better settling effect, reducing the amount of external flocculant used by 62.5%.

[0071] In this process, the minerals in the slurry are transformed into calcium magnesium (sulfite) crystals; under aeration or in the presence of dissolved oxygen, the Fe in the slurry... 2+ Converted to Fe 3+ Fe 3+ The various hydroxyl complexes produced by hydrolysis have excellent charge neutralization and bridging capabilities, and work synergistically with calcium magnesium (sulfite) crystals.

[0072] After desulfurization, the SO2 concentration at the flue gas outlet stabilized at 40 mg / m³. 3 The desulfurization efficiency reached 95%. The solid content of the tailings after desulfurization was 28.96 wt.%, and the pH value of the slurry was 7.2.

[0073] The resulting slurry system (the product of gas-solid separation) has calcium magnesium (sulfite) sulfite crystals as its framework, on which are loaded highly flocculating amorphous iron hydroxide gel and polynuclear hydroxy iron complex gel. The calcium magnesium (sulfite) sulfite crystals include calcium sulfite crystals, magnesium sulfite crystals, calcium sulfate crystals and magnesium sulfate crystals.

[0074] Example 3

[0075] An enhanced method for achieving self-flocculation and sedimentation separation of tailings based on flue gas desulfurization includes the following steps:

[0076] The iron tailings used have a pre-disposal capacity, with an alkaline component content as high as 28 wt.% (mainly CaO) and a TFe grade of 24.17%. After grinding to -325 mesh, 80% of the material is fine. The flue gas originates from non-ferrous metal smelting, with a temperature of 155℃ and an extremely high SO2 concentration of 4800 mg / m³. 3 .

[0077] (1) The pre-discarded iron tailings are slurried to obtain alkaline iron tailings slurry. The solid-liquid ratio of the slurry is 1:3, that is, the slurry concentration is 25wt.%. Utilizing its own alkalinity, the pH naturally reaches 11.5.

[0078] (2) The hot flue gas from roasting is mixed at a volume ratio of 20:1 (m³ / kg) 3 / L) is fed into the alkaline iron tailings slurry inside the bubble column to ensure sufficient reaction time for flue gas desulfurization. Simultaneously, the waste heat from the flue gas is used to heat the slurry exposed to air, maintaining a slurry temperature of 70°C to promote the reaction rate and oxygen dissolution (promoting oxidation). The alkaline minerals in the slurry are converted into sulfate crystals, which react with the Fe in the slurry. 2+ The amorphous ferric hydroxide gel and polynuclear hydroxy iron complex gel produced by oxidation and hydrolysis form components that can significantly enhance the sedimentation and separation effect, resulting in a slurry system with self-flocculation ability.

[0079] The resulting slurry system is directly added to a thickening tank for tailings sedimentation and separation. The initial settling rate of the tailings slurry reaches 4.8 m / h, requiring no external flocculant, achieving highly efficient sedimentation with "zero external flocculant" and significantly reducing operating costs.

[0080] In this process, the minerals in the slurry are transformed into calcium (sulfite) crystals; under aeration or in the presence of dissolved oxygen, the Fe in the slurry... 2+ Converted to Fe3+ Fe 3+ The various hydroxyl complexes produced by hydrolysis have excellent charge neutralization and bridging capabilities, and work synergistically with calcium (sulfite) crystals.

[0081] After desulfurization, the SO2 concentration at the flue gas outlet is below 190 mg / m³. 3 The desulfurization efficiency reached 96.04%. The solid content of the tailings after desulfurization was 20.48 wt.%, and the pH value of the slurry was 9.

[0082] The resulting slurry system (the product of gas-solid separation) has calcium (sulfite) crystals as its framework, on which are loaded highly flocculating amorphous ferric hydroxide gel and polynuclear hydroxy ferric complex gel. The calcium (sulfite) crystals include calcium sulfite crystals and calcium sulfate crystals.

[0083] Example 4

[0084] An enhanced method for achieving self-flocculation and sedimentation separation of tailings based on flue gas desulfurization includes the following steps:

[0085] Iron tailings from different stages of the concentrator were pre-enriched using a mixture of ore from various processing plants. The tailings contained 20 wt.% alkaline components (mainly MgO) and 12.56% TFe, and were ground to -325 mesh (75%). The flue gas was a mixture of roasting and sintering flue gas, with a temperature of 145℃ and an average SO2 concentration of 2500 mg / m³. 3 .

[0086] (1) The mixed pre-enriched iron tailings were slurried to obtain alkaline iron tailings slurry. The solid-liquid ratio of the slurry was 1:4, that is, the slurry concentration was 20wt.%. The pH was adjusted to 10.2 using NaOH or Ca(OH)2.

[0087] (2) The hot flue gas from roasting is mixed at a volume ratio of 35:1 (m³ / kg / kg / m³). 3 / L) Alkaline iron tailings slurry is introduced into the bubble column for flue gas desulfurization. Simultaneously, the waste heat from the flue gas is used to heat the slurry exposed to air, raising its temperature to 60°C. The alkaline minerals in the slurry are converted into sulfate crystals, which react with the Fe in the slurry. 2+ The amorphous ferric hydroxide gel and polynuclear ferric hydroxy complex gel produced by oxidation and hydrolysis form components that can significantly enhance sedimentation and separation effects, resulting in a slurry system with self-flocculation capabilities.

[0088] The resulting slurry system was directly added to a thickening tank for tailings sedimentation and separation. The tailings sedimentation rate reached 3.8 m / h, and the amount of external flocculant PAM was reduced by 50%, further lowering costs.

[0089] In this process, the minerals in the slurry are transformed into magnesium (sulfite) crystals; under aeration or in the presence of dissolved oxygen, the Fe in the slurry...2+ Converted to Fe 3+ Fe 3+ The various hydroxyl complexes produced by hydrolysis have excellent charge neutralization and bridging capabilities, and work synergistically with magnesium (sulfite) crystals.

[0090] After desulfurization, the SO2 concentration at the flue gas outlet is below 90 mg / m³. 3 The desulfurization efficiency reached 96.5%. The solid content of the tailings after desulfurization was 29.81 wt.%, and the pH value of the slurry was 6.8.

[0091] The resulting slurry system (the product of gas-solid separation) has magnesium (sulfite) crystals as its framework, on which are loaded highly flocculating amorphous ferric hydroxide gel and polynuclear hydroxy ferric complex gel. The magnesium (sulfite) crystals include magnesium sulfite crystals and magnesium sulfate crystals.

[0092] Example 5

[0093] An enhanced method for achieving self-flocculation and sedimentation separation of tailings based on flue gas desulfurization includes the following steps:

[0094] Hematite gravity separation tailings were used, with an alkaline component (CaO+MgO) content of 22 wt.% and a TFe grade of 19.49%, and were ground to -325 mesh (70%). The flue gas originated from the sintering mill head, with a temperature of approximately 150℃ and an SO2 concentration of 2000 mg / m³. 3 .

[0095] (1) The tailings of hematite gravity separation were slurried to obtain alkaline iron tailings slurry with a solid-liquid ratio of 1:4.5, i.e., a slurry concentration of about 18.2 wt.% and a slurry pH of 10.8.

[0096] (2) The hot flue gas was mixed at a volume ratio of 30:1 (m³ / kg) 3 / L) Alkaline iron tailings slurry is introduced into the bubble column for flue gas desulfurization. Simultaneously, the waste heat from the flue gas is used to heat the slurry exposed to air, raising its temperature to 65°C. The alkaline minerals in the slurry are converted into sulfate crystals, which react with the Fe in the slurry. 2+ The amorphous ferric hydroxide gel and polynuclear ferric hydroxy complex gel produced by oxidation and hydrolysis form components that can significantly enhance sedimentation and separation effects, resulting in a slurry system with self-flocculation capabilities.

[0097] The resulting slurry system was directly added to a thickening tank for tailings sedimentation and separation. The initial settling rate of the tailings slurry reached 3.6 m / h, which is about 3.3 times better than the untreated tailings slurry of the same batch (settling rate of about 1.1 m / h), and the settling performance can meet the requirements of subsequent pressure filtration without the need for external flocculants.

[0098] In this process, the minerals in the slurry are transformed into calcium magnesium (sulfite) crystals; under aeration or in the presence of dissolved oxygen, the Fe in the slurry... 2+ Converted to Fe 3+ Fe 3+ The various hydroxyl complexes produced by hydrolysis have excellent charge neutralization and bridging capabilities, and work synergistically with calcium magnesium (sulfite) crystals.

[0099] After desulfurization, the SO2 concentration at the flue gas outlet stabilized at 75 mg / m³. 3 The desulfurization efficiency reached 96.3%. The solid content of the tailings after desulfurization was 26.4 wt.%, and the pH value of the slurry was 7.6.

[0100] The resulting slurry system (the product of gas-solid separation) has calcium magnesium (sulfite) sulfite crystals as its framework, on which are loaded highly flocculating amorphous iron hydroxide gel and polynuclear hydroxy iron complex gel. The calcium magnesium (sulfite) sulfite crystals include calcium sulfite crystals, magnesium sulfite crystals, calcium sulfate crystals and magnesium sulfate crystals.

[0101] Example 6

[0102] An enhanced method for achieving self-flocculation and sedimentation separation of tailings based on flue gas desulfurization includes the following steps:

[0103] Siderite pre-enriched tailings were used, with an alkaline component content of 19 wt.% (mainly MgO) and a TFe grade of 16.37%, and 68% of the particles were ground to a particle size of -325 mesh. The flue gas was derived from the tail gas after blast furnace gas purification, with a flue gas temperature of approximately 130℃ and an SO2 concentration of 600 mg / m³. 3 .

[0104] (1) The siderite pre-selection tailings were slurried to obtain alkaline iron tailings slurry with a solid-liquid ratio of 1:5, i.e., a slurry concentration of about 16.7 wt.% and a slurry pH of 9.5.

[0105] (2) The hot flue gas is mixed at a volume ratio of 40:1 (m³ / kg) 3 / L) Alkaline iron tailings slurry is introduced into the bubble column for flue gas desulfurization. Simultaneously, the waste heat from the flue gas is used to heat the slurry exposed to air, achieving a slurry temperature of 55℃. The alkaline minerals in the slurry are converted into sulfate crystals, which react with the Fe in the slurry. 2+ The amorphous ferric hydroxide gel and polynuclear ferric hydroxy complex gel produced by oxidation and hydrolysis form components that can significantly enhance sedimentation and separation effects, resulting in a slurry system with self-flocculation capabilities.

[0106] The resulting slurry system is directly added to a thickening tank for tailings sedimentation and separation. The initial settling rate of the tailings slurry reaches 3.9 m / h. Compared with the original process that required the addition of a large amount of PAM (0.6 kg per ton of dry tailings), only 0.2 kg / t of PAM is now needed to achieve better settling effect, reducing the amount of external flocculant used by approximately 66.7%.

[0107] In this process, the minerals in the slurry are transformed into magnesium (sulfite) crystals; under aeration or in the presence of dissolved oxygen, the Fe in the slurry... 2+ Converted to Fe 3+ Fe 3+ The various hydroxyl complexes produced by hydrolysis have excellent charge neutralization and bridging capabilities, and work synergistically with magnesium (sulfite) crystals.

[0108] After desulfurization, the SO2 concentration at the flue gas outlet stabilized at 35 mg / m³. 3 The desulfurization efficiency reached 94.2%. The solid content of the tailings after desulfurization was 24.7 wt.%, and the pH value of the slurry was 7.0.

[0109] The resulting slurry system (the product of gas-solid separation) has magnesium (sulfite) crystals as its framework, on which are loaded highly flocculating amorphous ferric hydroxide gel and polynuclear hydroxy ferric complex gel. The magnesium (sulfite) crystals include magnesium sulfite crystals and magnesium sulfate crystals.

[0110] Example 7

[0111] An enhanced method for achieving self-flocculation and sedimentation separation of tailings based on flue gas desulfurization includes the following steps:

[0112] Iron tailings (containing hematite and limonite) were separated using a mixed weak magnetic separation method. The alkaline component (mainly CaO) content was 25 wt.%, and the TFe grade was 27.05%. After grinding, 78% of the material was reduced to a particle size of -325 mesh. The flue gas originated from non-ferrous metal smelting tail gas, with a temperature of approximately 170℃ and an SO2 concentration of 3500 mg / m³. 3 .

[0113] (1) Mixed weak magnetic iron tailings were slurried to obtain alkaline iron tailings slurry with a solid-liquid ratio of 1:3.5, i.e., slurry concentration of about 22.2 wt.% and slurry pH of 11.2.

[0114] (2) The hot flue gas was mixed at a volume ratio of 22:1 (m³ / kg) 3 / L) Alkaline iron tailings slurry is introduced into the bubble column for flue gas desulfurization. Simultaneously, the waste heat from the flue gas is used to heat the slurry exposed to air, raising its temperature to 75°C. The alkaline minerals in the slurry are converted into sulfate crystals, which react with the Fe in the slurry. 2+The amorphous ferric hydroxide gel and polynuclear ferric hydroxy complex gel produced by oxidation and hydrolysis form components that can significantly enhance sedimentation and separation effects, resulting in a slurry system with self-flocculation capabilities.

[0115] The resulting slurry system is directly added to a thickening tank for tailings sedimentation and separation. The initial settling rate of the tailings slurry reaches 4.2 m / h, requiring no external flocculant and achieving highly efficient sedimentation with "zero external addition".

[0116] In this process, the minerals in the slurry are transformed into calcium (sulfite) crystals; under aeration or in the presence of dissolved oxygen, the Fe in the slurry... 2+ Converted to Fe 3+ Fe 3+ The various hydroxyl complexes produced by hydrolysis have excellent charge neutralization and bridging capabilities, and work synergistically with calcium (sulfite) crystals.

[0117] After desulfurization, the SO2 concentration at the flue gas outlet is below 150 mg / m³. 3 The desulfurization efficiency reached 95.7%. The solid content of the tailings after desulfurization was 21.5 wt.%, and the pH value of the slurry was 8.2.

[0118] The resulting slurry system (the product of gas-solid separation) has calcium (sulfite) crystals as its framework, on which are loaded highly flocculating amorphous ferric hydroxide gel and polynuclear hydroxy ferric complex gel. The calcium (sulfite) crystals include calcium sulfite crystals and calcium sulfate crystals.

[0119] Example 8

[0120] An enhanced method for achieving self-flocculation and sedimentation separation of tailings based on flue gas desulfurization includes the following steps:

[0121] Phosphorus-containing pre-enriched iron tailings were used, with an alkaline component content of 17 wt.% (CaO + MgO) and a TFe grade of 21.78%. After grinding, 72% of the material was reduced to a particle size of -325 mesh. The flue gas was sourced from a coal-fired boiler, with a temperature of approximately 120℃ and an SO2 concentration of 1000 mg / m³. 3 .

[0122] (1) Phosphorus-containing iron tailings were slurried to obtain alkaline iron tailings slurry with a solid-liquid ratio of 1:4, i.e., slurry concentration of about 20 wt.% and slurry pH of 10.0.

[0123] (2) The hot flue gas was mixed at a volume ratio of 28:1 (m³ / kg) 3 / L) Alkaline iron tailings slurry is introduced into the bubble column for flue gas desulfurization. Simultaneously, the waste heat from the flue gas is used to heat the slurry exposed to air, maintaining a slurry temperature of 45℃. The alkaline minerals in the slurry are converted into sulfate crystals, which react with the Fe in the slurry. 2+The amorphous ferric hydroxide gel and polynuclear ferric hydroxy complex gel produced by oxidation and hydrolysis form components that can significantly enhance sedimentation and separation effects, resulting in a slurry system with self-flocculation capabilities.

[0124] The resulting slurry system is directly added to a thickening tank for tailings sedimentation and separation. The initial settling rate of the tailings slurry reaches 3.4 m / h. Compared with the original process that required the addition of a large amount of PAM (0.7 kg per ton of dry tailings), now only 0.25 kg / t of PAM is needed to achieve better settling effect, reducing the amount of external flocculant used by approximately 64.3%.

[0125] In this process, the minerals in the slurry are transformed into calcium magnesium (sulfite) crystals; under aeration or in the presence of dissolved oxygen, the Fe in the slurry... 2+ Converted to Fe 3+ Fe 3+ The various hydroxyl complexes produced by hydrolysis have excellent charge neutralization and bridging capabilities, and work synergistically with calcium magnesium (sulfite) crystals.

[0126] After desulfurization, the SO2 concentration at the flue gas outlet is below 50 mg / m³. 3 The desulfurization efficiency reached 95.0%. The solid content of the tailings after desulfurization was 27.3 wt.%, and the pH value of the slurry was 7.4.

[0127] The resulting slurry system (the product of gas-solid separation) has calcium magnesium (sulfite) sulfite crystals as its framework, on which are loaded highly flocculating amorphous iron hydroxide gel and polynuclear hydroxy iron complex gel. The calcium magnesium (sulfite) sulfite crystals include calcium sulfite crystals, magnesium sulfite crystals, calcium sulfate crystals and magnesium sulfate crystals.

[0128] The scope of protection of this invention is not limited to the embodiments described above. Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its scope and spirit. If these modifications and variations fall within the scope of this invention and its equivalents, then the intent of this invention also includes these modifications and variations.

Claims

1. An enhanced method for achieving self-flocculation and sedimentation separation of tailings based on flue gas desulfurization, characterized in that, Includes the following steps: The iron tailings obtained through physical sorting are slurry-adjusted to obtain alkaline iron tailings slurry. The flue gas from roasting or iron smelting is passed into an alkaline iron tailings slurry for desulfurization. Simultaneously, the waste heat from the flue gas is used to heat the slurry exposed to air, converting the alkaline minerals in the slurry into sulfate crystals, which then react with the Fe in the slurry. 2+ The amorphous ferric hydroxide gel and polynuclear ferric hydroxy complex gel produced by oxidation and hydrolysis are used to obtain a slurry system with self-flocculation ability. The obtained slurry system is directly added to a thickening tank for tailings sedimentation and separation.

2. The enhanced method for achieving tailings self-flocculation and sedimentation separation based on flue gas desulfurization according to claim 1, characterized in that, The iron tailings include magnetically separated iron tailings, pre-enriched iron tailings, pre-disposal iron tailings, and gravity separated iron tailings, with a TFe grade of >5% in the iron tailings.

3. The enhanced method for achieving tailings self-flocculation and sedimentation separation based on flue gas desulfurization according to claim 1, characterized in that, The alkaline component in the iron tailings is ≥15wt.%, and the tailings particles have a particle size of -325 mesh accounting for 60%~80%; the alkaline component includes one or more of CaO and MgO.

4. The enhanced method for tailings self-flocculation and sedimentation separation based on flue gas desulfurization according to claim 1, characterized in that, The solid-liquid ratio of the alkaline iron tailings slurry is 1:(3~5), and the pH value of the slurry is 9~12.

5. The enhanced method for achieving tailings self-flocculation and sedimentation separation based on flue gas desulfurization according to claim 4, characterized in that, When the pH value of the slurry is lower than 9, NaOH or Ca(OH)2 is added for adjustment.

6. The enhanced method for achieving tailings self-flocculation and sedimentation separation based on flue gas desulfurization according to claim 1, characterized in that, The SO2 concentration in the roasting or iron and steel smelting flue gas is 500 mg / m³. 3 ~5000mg / m 3 The volume ratio of flue gas to slurry is (20~40):1m³ 3 / L, slurry temperature is 30℃~80℃.

7. The enhanced method for achieving tailings self-flocculation and sedimentation separation based on flue gas desulfurization according to claim 1, characterized in that, SO2 concentration in flue gas after desulfurization ≤200mg / m³ 3 It meets the special emission limits specified in the "Emission Standard of Air Pollutants for Iron and Steel Sintering and Pelletizing Industry" (GB 28662-2012), with a desulfurization efficiency of ≥90%; the solid content of the tailings after desulfurization is 20wt.%~30wt.%, and the pH value of the slurry is 6~9.

8. The enhanced method for achieving tailings self-flocculation and sedimentation separation based on flue gas desulfurization according to claim 1, characterized in that, After the slurry system is directly added to the thickening tank for sedimentation, the initial sedimentation velocity of the tailings flocculation is ≥3m / h, and the amount of external flocculant used is reduced by more than 50% during the sedimentation process.

9. A slurry system with self-flocculation capability, prepared by the method of claim 1, wherein the slurry system contains sulfate crystals as a framework and amorphous ferric hydroxide gel and polynuclear ferric hydroxy complexes supported thereon, wherein the sulfate crystals are selected from calcium sulfite crystals, magnesium sulfite crystals, calcium sulfate crystals and magnesium sulfate crystals.

Citation Information

Patent Citations

  • Concentrating and dry stacking method of iron tailing slurry

    CN102553889A

  • Method for recovering copper sulfide and ferric hydroxide in auricupride acid wastewater through sulfidization method

    CN103145267A

  • Beneficiation method for tailing-free pond

    CN106334621A

  • Flue gas desulfurization and recycling utilization method based on smelting tailing slag

    CN107213774A

  • Method for iron-reinforced red mud dealkalization and iron separating and recovering

    CN109988902A